COMPARATIVE ASSESSMENT OF OCCUPATIONAL RADIATION EXPOSURE TO INDIVIDUALS IN RUSSIA AND ABROAD - A. Yu Medvedev (Радиационная гигиена)
The article provides a comparative assessment of exposure levels of the staff from selected occupational groups in Russia and the respective doses reported for the personnel in some foreign countries. The comparison of the average doses was performed at on a country level and with respect of the job category: nurse, radiographer, industrial radiographer. The analysis involved some relevant data according to the Integrated State System for Doses Control and Registration, the United Nations Scientific Committee on the Effects of Atomic Radiation, the National Dose Registry of Canada, the Federal Office for Radiation Protection of Germany, the Norwegian Radiation Protection Authority. The system for monitoring and registration of individual doses, and the reasons for higher levels of occupational exposure in Russia are discussed. Some recommendations on improving registration of occupational radiation exposure to individuals in forms of Federal Statistical Observation are given.